Perencanaan Kredit Investasi dalam Pengembangan Industri Kecil Menengah Pakan Ternak di PT AFI - Ronald Giok Tampubolon; Ma'mun Sarma; Sri Hartoyo (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2011)
Generally, small and medium scale industries  (SMI’s) are individual enterprises or a factories which is closed in operating the enterprise by just relying on very limited equity. To sustain the development of the enterprise needs a credit from a bank which is one of the important  source funds of the working of capital for the developing investment capital purchasing of goods capital. In general, the aims of the research is to know the requirements to obtain the credit on a special scale (1) Studying internal and external factors which influence the development of the PT AFI enterprise; (2) Analyzing the development enterprise plan and the importance source of the funds from outside in the form of investment credit for increasing the production capacity of PT AFI. Collecting data is conducted by a direct interview with an entrepreneur to look at the process and management policy. In reaching the work of internal factors; (1) general aspects, (2) management aspects, (3) production aspects, (4) marketing aspects, and (5) financial aspects. Where as the analysis methods which are used are: (1) financial analysis: a. liquidity ratio, b. leverage ratio, c. activity ratio, d. rentability ratio, and e. coverage ratio; (2) scoring investment by using the method: a. payback period, b. net present value, c. internal rate of return, and d. profitability index. External data which support the development of the enterprise obtained from the result of the research which covered laws, president instruction, regulation from the government institution that is Bank Indonesia and reading materials, for example, literature, report, internet and the result from scholarly paper.  Based on the result of the research showed external factors, for example increasing capacity of people’s purchasing because of price increase of oil  cost had begun to decrease and the market opportunity still opened because the feed requirement is still big. Internal factors showed positive development. They are: (1) Financial analysis which is based on the result of selling data for the last five years, it obtained financial prediction, they are among other: a. liquidity ratio 2,23 times complied with minimal requirement, b. leverage ratio 2,01 times, complied with maximal requirement, c. activity ratio showed positive trend, d. rentability ratio showed positive trend, and e. coverage ratio showed positive trend; (2) Whereas based on the scoring the result obtained, they are: a. payback period 4 years 3 months, b. net present value > 0, meaning the proper project, c. internal rate of return > rate of return meaning proper project, and d. profitability index > 1, meaning feasible project. Whereas based on the sensitivity analysis assuming that the sale decreased 10%; production decreased 10% and the general sale cost and administration increased 2%, turning out that it hasn’t influence the project feasibility sensitivity yet. All this condition will certainly  become positive value for a bank which in conducting its enterprise requires a risk management application so that it will operated more prudential, especially avoiding the payment failure risk from counterparty